Nursing Intervention Classifications (NIC) validated for patients at risk of pressure ulcers (Revista Latino-Americana de Enfermagem, 2012)
OBJECTIVE: to validate the Nursing Intervention Classifications (NIC) for the diagnosis 'Risk of Impaired Skin Integrity' in patients at risk of pressure ulcers (PU). METHOD: the sample comprised 16 expert nurses. The data was collected with an instrument about the interventions and their definitions were scored on a Likert scale by the experts. The data was analyzed statistically, using the calculation of weighted averages (WA). The study was approved by the Research Ethics Committee (56/2010). RESULTS: nine interventions were validated as 'priority' (WA ≥0.80), among them Prevention of PU (MP=0.92); 22 as 'suggested' (WA >0.50 and